SAT0483 Ultrasonography Changes during The Course of Septic Arthritis Are Associated with Functional Outcome. (15th July 2016) - Gaigneux, E.; Cormier, G.; Merot, O.; Maugars, Y.; Le Goff, B.
Abstract : Background: Ultrasonography (US) is useful to study the joints and the synovial tissue. It allows the evaluation of the synovial membrane thickness and inflammation. It can depict effusions and help to assess the surrounding soft tissues. Therefore, US could be of interest in the monitoring of septic arthritis. Objectives: The main goal of this study was to describe the US changes observed during the course of septic arthritis and their association with clinical and functional outcomes. Methods: We included all patients seen for a native joint infection in 3 different hospitals between January 2014 and July 2015. We collected baseline demographic, clinical, biological and microbiological characteristics. Patients were followed up prospectively with clinical and US evaluation at Day 0, 4, 15 and at 3 months (M3). US exam included the study of synovial membrane thickness, Power Doppler and involvement of the periarticular tissue. Evolution of the synovial thickness was compared to baseline (% of change). X-Ray of the joint was made at baseline and M3. Functional outcome was assessed at M3 (range of motion; SF-36 score). Results: Thirty four patients were included, mean age 63.7 (range 22–90) with 24 men (70.6%). Most of the time, septic arthritis occurred in patients with pre-existing joint disease (n=24; 70.6%) and the knee was mostly affected (n=19; 55.9%). Predominant causative organism was Staphylococcus Aureus (n=15; 44.1%). Twelve patients (35.3%) underwent joint lavage mean time 4.2 days (range 0–13) after the diagnosis with synovectomy in 2 cases (5.9%). US synovitis was present in 96.4% of the cases at D0, 100% at D15 but was less frequent at M3 (77.8%; p=0.051). The synovial thickness increased at D4 and D15 compared to baseline (respectively median +17.3%, +20%, p=0.015) and significantly decreased at M3 (median -31.5%; p=0.015). Doppler signal was frequent (64.3% (D0); 66.7% (D4); 61.3% (D15)) and decreased significantly at M3 (25.9%; p=0.04). The effusion was present at D0 (92.8%), D4 (88.9%), D15 (80.6%) and significantly less frequent at M3 (55.6%, p=0.001). Periarticular abscess or cellulitis was rare (10.7% and 3.7% at D0 respectively). At M3, one patient died (2.9%) and 5 (14.7%) patients were lost to follow-up. Twenty (58.8%) patients had a decreased joint range of motion. A high total Sharp score and a high joint space narrowing score at M3 was associated with a late start antibiotic treatment (respectively p=0.048, p=0.03). We found no correlation between US characteristics and any of the baseline clinical or biological parameters. In contrast, joint limitation at M3 was associated with an increase of the synovial thickness between D0 and M3 (p=0.024) and with the persistence of Doppler at D15 and at M3 ((p=0.033; p=0.002). Conclusions: Septic arthritis have a poor functional outcome in more than half of the cases. US synovitis remains present at 3 months in most patients but with a significant decrease in synovial thickness compared to baseline. Doppler signal persists in a quarter of the cases at M3. Persistence of Doppler signal and a thickened synovial tissue at 3 months are associated with a poor clinical outcome. Disclosure of Interest: None declared